2020
DOI: 10.1017/s1751731120000889
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal fermentation characteristics and related feeding values of compound feeds and their constituting single feeds studied by using in vitrotechniques

Abstract: Single concentrate feeds are mixed together forming compound feeds for cattle. However, knowledge regarding the potential interactions (associative effects) between the feeding values of single feeds in compound feeds is lacking. The main objective of the present study was to evaluate ruminal fermentation characteristics and feeding values of eight industrially produced compound feeds in mash form from their constituent single feeds for dairy cows through in vitro assays. Additivity was given for gas productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In vitro rumen-simulated fermentation techniques are commonly used to evaluate the extent of rumen microbial fermentation and the utilization of diets ( Yejun et al, 2019 ; Grubješić et al, 2020 ; Choi et al, 2021 ). Rumen microorganisms ferment carbohydrates to produce rumen gasses (H 2 , CH 4 , CO 2 , etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In vitro rumen-simulated fermentation techniques are commonly used to evaluate the extent of rumen microbial fermentation and the utilization of diets ( Yejun et al, 2019 ; Grubješić et al, 2020 ; Choi et al, 2021 ). Rumen microorganisms ferment carbohydrates to produce rumen gasses (H 2 , CH 4 , CO 2 , etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, granulation results in the more efficient degradation of crude protein and starch in the rumen in some compound feeds than in the crushed form of compound feed, which may be due to the departure of ungraded finer feed particles from the bag (Grubjesic et al 2019). Afterwards, the single feed data on GP 24h , metabolic energy, OMD and available CP in the duodenum have additivity, however the data are not additive on intestinal digestibility of undegraded protein in the rumen, so the degradation of CP in compound feed in the rumen cannot be forecasted reliably by CP fractions (Grubjesic et al 2020). Yuan and Wan (2019) reported that when peanut shell was combined with concentrate and alfalfa, the best combinations of single-factor and multiple-factor associative effects index were 30 : 10 : 60 and 40 : 30 : 30 (concentrate/peanut shell/alfalfa ratios).…”
Section: Ammonia Nitrogen and Vfa Of Feed Mixturesmentioning
confidence: 99%
“…However, Grubjesic et al (2019) suggested that in most cases, pelleting led to the greater effective ruminal deg-Czech Journal of Animal Science, 65, 2020 (10): 389-401 https://doi.org/10.17221/165/2020-CJAS radation of crude protein and starch in some compound feeds than in compound feeds in mash form, probably due to undegraded finer feed particles which leave the bags. Afterwards, Grubjesic et al (2020) concluded that when formulating compound feeds for cattle, single feed data for GP 24 h , OMD, metabolizable energy (ME) and utilizable CP in the duodenum are additive, while those for intestinal digestibility of rumen undegraded protein are not, therefore, using CP fractions did not reliably predict the in situ ruminal CP degradation of compound feeds. The above four reports showed once again that the AE between feeds is widespread, but the mechanism of the AE between feeds is very complex.…”
Section: Original Papermentioning
confidence: 99%